Ekologi Politik: Studi Tentang Dampak Kebijakan Pengelolaan Sampah di TPA Binuang Kab. Polewali Mandar - Taufiq Akbar Hidayat; Gustiana Kambo; Muhammad Imran (Journal of Peace, Security and Democracy, 2026)
Waste management at the Binuang Landfill has earned Polewali Mandar Regency the Adipura Award. However, waste management at the Binuang Landfill has resulted in leachate seeping into community rice fields and air pollution. This environmental pollution impacts the socio-economic aspects of the community. This study aims to analyze the impact of waste management policies at the Binuang Landfill on the environment and surrounding community using the concept of Political Ecology. This study uses a qualitative approach with descriptive methods. Data were collected through interviews, observations, and documentation. The results of this study indicate that waste management policies at the Binuang Landfill do not yet reflect the principles of sustainable and equitable political ecology. This can be observed in the environmental position in policy negotiations between the government and the community. The conflict between the government and the community focuses solely on fulfilling their respective rights without considering environmental aspects. This condition makes waste management at the landfill suboptimal, resulting in impacts that sacrifice the rights and welfare of the community around the Binuang Landfill.